Randomized Trial of Fetal Surgery for Moderate Left Diaphragmatic Hernia. Issue 1 (23rd March 2022) - Deprest, J.A.; Benachi, A.; Gratacos, E.; Nicolaides, K.; Berg, C.; Persico, N.; Belfort, M.; Gardener, G.J.; Ville, Y.; Johnson, A.; Morini, F.; Wielgoś, M.; et al.
Abstract : ( N Engl J Med . 2021;385:119–129) Congenital diaphragmatic hernia (CDH) can lead to pulmonary hypoplasia and is associated with serious neonatal complications and death. In infants with severe left diaphragmatic hernia, fetoscopic endoluminal tracheal occlusion (FETO) has been associated with greater survival rates but also higher rates of premature birth. This study aimed to determine the effects of FETO on pregnancies affected by moderate CDH compared with expectant prenatal care.